Quantitative and Qualitative Approach of Banking Performance measure Based on Job Satisfaction for Islamic and Conventional banks in Indonesia - Mr Amrizal (BALANCE: Economic, Business, Management and Accounting Journal, 2016)
ABSTRACT  This study aims to fill in the gap on by identifying the performance measurement based on job satisfaction for Islamic and conventional banks in Indonesia. The study then investigates the influences of achievement, Recognition, work itself, responsibility and advancement to ward job satisfaction. This study is based on the Herzberg's theory , applying both quantitative and qualitative research design. Objects of research consist of three Islamic and conventional banks in Indonesia. For the quantitative analysis, respondents consist of 900 employees from Islamic and conventional banks in Indonesia, taking snowball sampling as the sample technique. Data garnered is analyzed, adopting confirmatory factory analysis research with Amos version 22. As for the qualitative data, informants consist of 18 human resource and technology managers of Islamic and conventional banks, taking purposive sampling as the sample technique. Researcher uses interview to collect data qualitative meanwhile data analysis use narrative analysis. Quantitative analysis found that partially all indicators of achievement, Recognition, work itself, responsibility and advancement have positive significant relationship and very strong influence for Islamic and conventional banks. Results of analysis of qualitative data confirms the quantitative findings; service trends and innovations in banking industries such as  achievement, Recognition, work itself, responsibility and advancement continue to raise job satisfaction expectations of service quality. Majority of the banks are raising this performance, evidenced by the increase in the number of service improvement initiatives rolled out by banks. This study implicates that, for managers to be able to gauge improved performance. They have to be able to identify and focus on employee who presents clear potential for long-term and mutually beneficial relationships.Keyword : Job satisfaction, Performance, Islamic banks, Conventional BanksCorrespondence to : amrizalusim@gmail.com